Literasi Baca Tulis Pada Siswa Yang Memiliki Gaya Belajar Auditorial di Kelas IV SD Inpres Ranowangko - Mombilia, Natalia T.; Tuerah, Roos M. S. M.S.; Tumurang, Hetty J. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was conducted based on the results of research findings during observations in class IV of SD Inpres Ranowangko. The aim of this research is to describe the implementation of reading and writing literacy for students with an auditory learning style, problems with implementing reading and writing literacy for students with an auditory learning style, as well as efforts in overcoming barriers to reading and writing literacy in students who have an auditory learning style. To realize the research objectives, this research was designed using descriptive qualitative methods. The research methods used are observation, interviews and documentation. The results of this research were that it was found that the implementation of reading and writing literacy for students with a learning style was not yet optimal, and there were several obstacles in implementing reading and writing literacy for students with an auditory learning style, if seen from the indicators and basic principles of developing and implementing reading and writing literacy. including: reading and writing literacy activities are not balanced with the situation and circumstances at school. low family participation, lack of updates to reading materials, minimal availability of school facilities, minimal mastery of literacy and numeracy teaching staff, low intensity of implementation of reading and writing literacy, no PISA, PIRLS and INAP assessments, lack of variety of reading materials, lack of literacy school activities, and there is no written work from both students and teachers, low levels of parental and community involvement, and no study groups at school.